Method for in-situ growth of Ti < 3 > C < 2 > T < x >-titanium dioxide heterogeneous interface material and application
The in-situ growth of Ti3C2Tx-titanium dioxide heterointerface material by oxygen microwave plasma treatment solves the problem of limited application of existing gas sensors in wearable devices, and achieves high sensitivity and selective hydrogen detection.
Patent Information
- Application Number
- CN202411661547.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-11-20
AI Technical Summary
Existing metal oxide semiconductor gas sensors are limited in applications in wearable devices due to high operating temperatures, long response time, poor selectivity and wide spectral response to gases similar to redox characteristics.
The Ti3C2Tx-titanium dioxide heterointerface material was grown in situ by oxygen microwave plasma treatment, and the Ti3C2Tx material was prepared by hydrothermal etching Ti3AlC2 and oxidizing it in the oxygen microwave plasma to form a two-dimensional sheet-shaped TiO2 nanosheets tightly wrapped around the surface of Ti3C2Tx to form a Ti3C2Tx-TiO2 heterointerface material.
It improves gas sensitivity performance, enhances the response and selectivity to hydrogen, and has simple treatment methods, low energy consumption, high material stability, and short response recovery time.
Smart Images

Figure CN119774614A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of two-dimensional composite materials and gas sensors, and in particular to an in-situ grown Ti 3 C 2 Methods and applications of Tx-titanium dioxide heterogeneous interface materials. Background Art
[0002] As a clean, environmentally friendly, renewable and abundant energy source, hydrogen has become one of the most promising candidates for the next generation of energy. However, hydrogen is highly explosive and flammable, and extreme caution is required during its preparation, storage, transportation and application to prevent leakage. Therefore, the development of highly sensitive and selective hydrogen sensors with rapid detection and recovery is essential to detect and mitigate potential hazards associated with hydrogen storage, transportation and leakage. Metal oxide semiconductor (MOS) gas sensors are a widely used type of sensor with advantages such as low cost, small size, easy integration and real-time monitoring. However, the application of these sensors in wearable sensing devices is limited by several issues, such as high operating temperature, long response time, poor selectivity and wide spectral response to gases with similar redox properties.
[0003] Mxene is a new type of two-dimensional transition metal carbide or nitride with a two-dimensional layered structure similar to graphene. It has a large specific surface area and good conductivity, stability, magnetic properties and mechanical properties. It can be widely used in catalysis, energy storage, adsorption and other fields. Its chemical formula is M n+1 X n T x , where M is a transition metal element, X is carbon or nitrogen, T x -F, -OH, -O and other functional groups linked to the surface, n = 1, 2, 3. The preparation of MXene is usually prepared by selectively etching away the A element in the MAX phase using a chemical liquid phase method. There are a large number of functional groups on the surface of MXene, which, on the one hand, provide abundant active sites for gas adsorption and surface reaction, and on the other hand, can interact specifically with specific gas molecules, thereby achieving selective adsorption. However, the low response value limits its application in the field of hydrogen sensing.
[0004] The use of metal oxide and MXene composite materials to prepare gas sensors can improve the gas sensing performance of MXene. The main reason for the performance improvement is that two different materials are combined to form a heterojunction. Therefore, when the sensor captures the gas molecules being measured, a depletion layer and a hole accumulation layer that can regulate electron transport are formed. At present, there have been some studies in the field of room temperature gas sensors using two-dimensional materials MXene composite metal oxide semiconductor materials. Partial oxidation of MXene to grow the corresponding oxide in situ is a simple method to construct a composite material of metal oxide and MXene. For example, Peng et al. [Hybrids of Two-Dimensional Ti 3 C 2 and TiO 2 Exposing{001}Facets toward EnhancedPhotocatalytic Activity, ACS Appl.Mater.Interfaces 2016,8,6051-6060] by Ti 3 C 2 T x TiO was synthesized by a simple hydrothermal reaction and partial oxidation in situ growth. 2 Nanosheet Ti 3 C 2 T x Hybrid composed of TiO 2 Although the nanosheets were successfully grown, Ti 3 C 2 T x The lamellar structure also collapsed. Summary of the invention
[0005] In order to solve the above technical problems, the present invention proposes a method for in-situ growth of Ti 3 C 2 Methods and applications of Tx-titanium dioxide heterogeneous interface materials.
[0006] To achieve the above object, the present invention provides the following technical solutions:
[0007] One of the technical solutions of the present invention:
[0008] An in-situ grown Ti 3 C 2 Tx-TiO2 heterogeneous interface material (Ti 3 C 2 Tx-TiO 2 The method of using a hydrochloric acid solution containing a fluorine compound as an etching solvent is to use a hydrothermal method to etch Ti 3 AlC 2 Preparation of Ti3 C 2 Tx materials, where x = -F, -OH and -O;
[0009] For the Ti 3 C 2 The Tx material is subjected to oxygen microwave plasma treatment to obtain the Ti 3 C 2 Tx-TiO 2 Heterogeneous interface materials;
[0010] When oxygen microwave plasma treatment is performed, the microwave power is 500-800W;
[0011] The oxygen microwave plasma treatment is carried out in an atmosphere of oxygen-argon mixed gas, wherein the volume fraction of oxygen in the oxygen-argon mixed gas is 10-30%.
[0012] The present invention uses Ti 3 AlC 2 As a MAX precursor, Ti was synthesized by hydrothermal method. 3 C 2 Tx material (x = -F, -OH or -O), then Ti 3 C 2 The Tx material was treated with low power (500-800W) oxygen microwave plasma to make Ti 3 C 2 The Tx material is partially oxidized to a two-dimensional TiO sheet 2 Oxide, 2D TiO flakes 2 The oxide is tightly wrapped around Ti 3 C 2 Tx surface, forming Ti 3 C 2 Tx-TiO 2 Heterogeneous interface materials, using Ti 3 C 2 Tx-TiO 2 The gas sensor made of heterogeneous interface materials has a good response to hydrogen. In the process of oxygen microwave plasma treatment, by controlling the lower microwave power and lower oxygen volume fraction, Ti 3 C 2 The slow oxidation of Tx is more conducive to its formation of a flaky structure.
[0013] The principle of the present invention is: using oxygen microwave plasma as activation energy to provide an oxygen condition for the material. Under the bombardment of oxygen microwave plasma, the oxygen in the plasma will react with Ti 3 C 2 The -F functional groups on the surface of Tx compete with each other and gradually replace them. The fluorine atoms that are released will be adsorbed on the initially oxidized TiO2 Surface, inhibiting TiO 2 The crystal grows along the (001) direction, thus forming TiO 2 Nanosheets. Finally, Ti with heterojunction surface is generated. 3 C 2 T x -TiO 2 Composite materials. The two-dimensional sheet structure has a higher specific surface area due to its thin planar structure, which is conducive to the adsorption of gas molecules and provides more active sites for surface reactions, thereby improving gas sensing performance. The construction of heterojunctions will cause band bending, promote the separation of electron-hole carriers, provide more carriers for gas-sensitive reactions, and thus improve the gas-sensitive performance of the material.
[0014] Preferably, Ti is grown in situ 3 C 2 Tx-TiO 2 In the method for preparing a heterogeneous interface material, when oxygen microwave plasma treatment is performed, the microwave power is 500-700W, and more preferably the microwave power is 700W.
[0015] Preferably, Ti is grown in situ 3 C 2 Tx-TiO 2 In the method of preparing heterogeneous interface materials, the concentration of hydrochloric acid in the hydrochloric acid solution containing fluorine compounds is 4-12 mol / L, and the concentration of the fluorine-containing compounds is 1-2 mol / L. The appropriate concentrations of hydrochloric acid and fluorine-containing compounds can convert the precursor Ti 3 AlC 2 The Al in the sample is completely etched to obtain a two-dimensional accordion-shaped Ti 3 C 2 Tx.
[0016] The fluorine-containing compound is LiF, NH 4 One of F and NaF.
[0017] Preferably, Ti is grown in situ 3 C 2 Tx-TiO 2 In the method of heterogeneous interface material, the temperature of the hydrothermal method is 120-180° C. and the time is 1-5 days.
[0018] Preferably, Ti is grown in situ 3 C 2 Tx-TiO 2 In the method for preparing heterogeneous interface materials, the oxygen microwave plasma treatment time is 10-60 minutes. If the oxygen microwave plasma treatment time is too short, the lamellar TiO 2 Incomplete generation, too long oxygen microwave plasma treatment time, resulting in excessive oxidation of Ti3 C 2 The Tx accordion-like structure collapses, which is not conducive to the adsorption of gas molecules, resulting in no obvious improvement in the gas-sensing performance of the material.
[0019] Preferably, Ti is grown in situ 3 C 2 Tx-TiO 2 In the method of heterogeneous interface material, the pressure during oxygen microwave plasma treatment is 100-1000 Pa, more preferably 500-1000 Pa. The intensity of microwave plasma has a certain relationship with pressure. The appropriate pressure range is to control the intensity of oxygen microwave plasma, thereby controlling Ti 3 C 2 The degree of oxidation of Tx.
[0020] The second technical solution of the present invention:
[0021] The present invention also provides a Ti obtained by in-situ growth according to the above method. 3 C 2 Tx-TiO 2 Heterogeneous interface materials.
[0022] The third technical solution of the present invention:
[0023] The present invention also provides the Ti 3 C 2 Tx-TiO 2 Application of heterogeneous interface material in the preparation of gas sensors, wherein the gas sensor is a hydrogen sensor.
[0024] The hydrogen sensor prepared by the present invention is Ti 3 C 2 T x / TiO 2 The heterogeneous interface material is a sensitive material, and the two-dimensional sheet structure has a higher specific surface area due to its thin planar structure, which is conducive to the adsorption of hydrogen molecules and provides more active sites for surface reactions, thereby improving the gas sensing performance.
[0025] The fourth technical solution of the present invention:
[0026] The present invention also provides a method for preparing a hydrogen sensor, comprising: 3 C 2 Tx-TiO 2 The heterogeneous interface material is mixed with alcohol, ground and deposited on a substrate containing an electrode (the alcohol will volatilize during the grinding process), and dried to obtain the hydrogen sensor.
[0027] Preferably, in the method for preparing a hydrogen sensor, the substrate comprises aluminum oxide (Al 2 O3 )、ZrO 2 ), polyimide (PI) and polyethylene terephthalate (PET). 2 O 3 With high resistance and thermal stability, Ti 3 C 2 Tx-TiO 2 Heterogeneous interface materials are easy to grow on it; ZrO 2 It is also a material with good insulation properties and can be used as a sensor substrate; PI has good heat resistance, excellent transparency, and excellent insulation. At the same time, PI also has good dimensional stability, flexibility, and solvent resistance; PET, as a polymer plastic, has the characteristics of low cost, light weight, transparency, and good flexibility. Flexible PFT can reduce the influence of thermal effects on the deformation and electrical instability of plastic substrates. Hydrogen sensors prepared on flexible substrates (such as PI and PET) can adapt to special environments. In short, using the above materials as substrates can affect the structure and mechanical properties of hydrogen sensors to a certain extent, thereby improving the overall performance of hydrogen sensors.
[0028] Preferably, in the method for preparing the hydrogen sensor, the deposition process includes screen printing, spraying, spin coating or drop coating.
[0029] Preferably, in the method for preparing a hydrogen sensor, the drying temperature is 50-100° C., and the drying time is 6-12 h.
[0030] Compared with the prior art, the present invention has the following advantages and technical effects:
[0031] (1) The present invention proposes a new type of Ti 3 C 2 Tx-TiO 2 The preparation method of heterogeneous interface material uses low-power oxygen microwave plasma as activation energy to provide an oxygen condition for the material. Under the bombardment of oxygen microwave plasma, the two-dimensional Ti 3 C 2 The Tx material will be partially oxidized to the corresponding TiO 2 Nanosheets, forming Ti 3 C 2 Tx-TiO 2 Heterogeneous interface materials. Ti 3 C 2 T x During the oxygen plasma treatment, the oxygen in the plasma will react with Ti 3 C 2 T xThe -F functional groups on the surface compete with each other and gradually replace them. The detached F atoms are adsorbed on the anatase TiO2 that is initially oxidized. 2 Particle surface, inhibiting TiO 2 Crystal growth along the (001) direction produces two-dimensional TiO 2 Nanosheets.
[0032] (2) Ti prepared by the method of the present invention 3 C 2 Tx-TiO 2 Heterogeneous interface materials have a unique structure. From the morphology point of view, Ti 3 C 2 TiO generated by partial oxidation of Tx 2 It is a two-dimensional nanosheet, TiO 2 Tightly wrapped in Ti 3 C 2 Tx surface. The two-dimensional sheet structure has a higher specific surface area due to its thin planar structure, which is beneficial to the adsorption of gas molecules and provides more active sites for surface reactions, thereby improving the gas sensing performance.
[0033] (3) The low-power oxygen microwave plasma treatment method used in the present invention is simple, low energy consumption, and the obtained Ti 3 C 2 Tx-TiO 2 The heterogeneous interface material has high stability and is resistant to H in a wide concentration range. 2 It has a higher response value and a faster response recovery time. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the accompanying drawings:
[0035] Figure 1 The Ti prepared by the hydrothermal method in Example 1 3 C 2 Topography of Tx.
[0036] Figure 2 The oxygen microwave plasma treatment of Ti in Example 1 3 C 2 Ti prepared after Tx 3 C 2 Tx / TiO 2 Morphology of heterogeneous interface materials.
[0037] Figure 3 Ti in Comparative Example 1 3 C 2 Tx-TiO2 Morphology of heterogeneous interface materials.
[0038] Figure 4 Ti in Comparative Example 2 3 C 2 Tx-TiO 2 Morphology of heterogeneous interface materials.
[0039] Figure 5 Ti in Comparative Example 3 3 C 2 Tx / TiO 2 Morphology of heterogeneous interface materials.
[0040] Figure 6 is Ti in Example 1 3 C 2 Tx-TiO 2 Response recovery curve of hydrogen sensor prepared by heterogeneous interface material to 1000 ppm hydrogen.
[0041] Figure 7 is Ti in Example 1 3 C 2 Tx-TiO 2 The sensor prepared by heterogeneous interface material is sensitive to 1000ppm H 2 , C 2 H 6 O、SO 2 , CH 4 ,CO,CO 2 The response value of . DETAILED DESCRIPTION
[0042] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0043] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0044] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0045] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.
[0046] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0047] Unless otherwise specified, the room temperature in the present invention is 25±2°C.
[0048] All raw materials used in the examples of the present invention are commercially available.
[0049] It should be pointed out that the matters not described in detail in the present invention are all conventional operating means in the field and are not the focus of the present invention. For example, specific methods such as screen printing, spraying, spin coating or drip coating are all completed using conventional methods.
[0050] The technical solution of the present invention is further illustrated by the following embodiments.
[0051] Example 1
[0052] The MAX precursor Ti 3 AlC 2 Add to 80mL of 4mol / L hydrochloric acid and 1mol / L LiF mixed solution, stir evenly and transfer to a 100mL polytetrafluoroethylene-lined stainless steel reactor, hydrothermally react at 120℃ for 5 days, centrifuge, wash and dry after cooling to obtain Ti 3 C 2 Tx (x = -F, -OH, -O) powder; the obtained Ti 3 C 2 The Tx powder was placed in a microwave plasma device, and an oxygen-argon mixed gas with an oxygen content of 20% (i.e., the volume fraction of oxygen in the oxygen-argon mixed gas was 20%) was introduced. The pressure was controlled at 500 Pa, and the power was turned on to control the power to 700 W. After oxygen plasma treatment for 40 minutes, the powder was taken out to obtain Ti 3C 2 Tx-TiO 2 Heterogeneous interface materials;
[0053] Ti 3 C 2 Tx-TiO 2 The heterogeneous interface material was mixed with alcohol, ground and deposited on an aluminum oxide substrate containing an electrode by screen printing, and dried at 80°C for 6 h to obtain a Ti 3 C 2 Tx-TiO 2 Hydrogen sensor with heterogeneous interface material as sensitive material.
[0054] Example 2
[0055] The MAX precursor Ti 3 AlC 2 Add to 80mL of 6mol / L hydrochloric acid and 1.5mol / L LiF mixed solution, stir evenly and transfer to 100mL polytetrafluoroethylene-lined stainless steel reactor, hydrothermally react at 140℃ for 3 days, centrifuge, wash and dry after cooling to obtain Ti 3 C 2 Tx (x = -F, -OH, -O) powder; the obtained Ti 3 C 2 The Tx powder was placed in a microwave plasma device, and an oxygen-argon mixed gas with an oxygen content of 20% was introduced. The pressure was controlled at 1000 Pa, and the power was turned on to control the power to 700 W. After oxygen plasma treatment for 40 minutes, the powder was taken out to obtain Ti 3 C 2 Tx-TiO 2 Heterogeneous interface materials;
[0056] Ti 3 C 2 Tx-TiO 2 The heterogeneous interface material was mixed with alcohol, ground and deposited on an aluminum oxide substrate containing an electrode by screen printing, and dried at 100°C for 6 hours to obtain a Ti 3 C 2 Tx-TiO 2 Hydrogen sensor with heterogeneous interface material as sensitive material.
[0057] Example 3
[0058] The MAX precursor Ti 3 AlC 2Add to 80mL of 8mol / L hydrochloric acid and 1mol / L LiF mixed solution, stir evenly and transfer to a 100mL polytetrafluoroethylene-lined stainless steel reactor, hydrothermally react at 120℃ for 4 days, centrifuge, wash and dry after cooling to obtain Ti 3 C 2 Tx (x = -F, -OH, -O) powder; the obtained Ti 3 C 2 The Tx powder was placed in a microwave plasma device with a power of 500W, an oxygen-argon mixture with an oxygen content of 10% was introduced, the pressure was controlled at 500Pa, the power was turned on, and the oxygen plasma treatment was carried out for 40 minutes before the powder was taken out to obtain Ti 3 C 2 Tx-TiO 2 Heterogeneous interface materials;
[0059] Ti 3 C 2 Tx-TiO 2 The heterogeneous interface material was mixed with alcohol, ground and then deposited on a zirconia substrate containing an electrode by drop coating. After drying at 80 ° C for 6 h, a Ti 3 C 2 Tx-TiO 2 Hydrogen sensor with heterogeneous interface material as sensitive material.
[0060] Example 4
[0061] The MAX precursor Ti 3 AlC 2 Add to 80mL of 4mol / L hydrochloric acid and 1mol / L LiF mixed solution, stir evenly and transfer to a 100mL polytetrafluoroethylene-lined stainless steel reactor, hydrothermally react at 120℃ for 5 days, centrifuge, wash and dry after cooling to obtain Ti 3 C 2 Tx (x = -F, -OH, -O) powder; the obtained Ti 3 C 2 The Tx powder was placed in a microwave plasma device, and an oxygen-argon mixed gas with an oxygen content of 30% was introduced. The pressure was controlled at 500 Pa, and the power was turned on to control the power to 800 W. After oxygen plasma treatment for 40 minutes, the powder was taken out to obtain Ti 3 C 2 Tx-TiO 2 Heterogeneous interface materials;
[0062] Ti 3 C 2 Tx-TiO 2The heterogeneous interface material was mixed with alcohol, ground and deposited on the PI substrate containing the electrode by spin coating, and dried at 50°C for 12 h to obtain a Ti 3 C 2 Tx-TiO 2 Hydrogen sensor with heterogeneous interface material as sensitive material.
[0063] Example 5
[0064] The MAX precursor Ti 3 AlC 2 Add to 80mL of 12mol / L hydrochloric acid and 2mol / L LiF mixed solution, stir evenly and transfer to 100mL polytetrafluoroethylene-lined stainless steel reactor, hydrothermally react at 180℃ for 1 day, centrifuge, wash and dry after cooling to obtain Ti 3 C 2 Tx( X =-F, -OH, -O) powder; the obtained Ti 3 C 2 The Tx powder was placed in a microwave plasma device, and an oxygen-argon mixed gas with an oxygen content of 10% was introduced. The pressure was controlled at 100 Pa, and the power was turned on to control the power to 700 W. After oxygen plasma treatment for 60 minutes, the powder was taken out to obtain Ti 3 C 2 Tx-TiO 2 Heterogeneous interface materials;
[0065] Ti 3 C 2 Tx-TiO 2 The heterogeneous interface material was mixed with alcohol, ground and then deposited on a PET substrate containing electrodes by spraying. After drying at 100 °C for 6 h, a Ti 3 C 2 Tx-TiO 2 Hydrogen sensor with heterogeneous interface material as sensitive material.
[0066] Comparative Example 1
[0067] The difference between this comparative example and Example 1 is that Ti 3 C 2 Tx was not subjected to oxygen microwave plasma treatment, but was placed in a conventional tube furnace and heated for 40 min in an oxygen-argon mixed atmosphere with an oxygen content of 20%. The specific method was as follows:
[0068] The MAX precursor Ti 3 AlC 2Add to 80mL of 4mol / L hydrochloric acid and 1mol / L LiF solution, stir evenly and transfer to a 100mL polytetrafluoroethylene-lined stainless steel reactor, hydrothermally react at 120℃ for 5 days, centrifuge, wash and dry after cooling to obtain Ti 3 C 2 T x The obtained Ti 3 C 2 T x The powder was placed in a tube furnace, and an oxygen-argon mixed gas with an oxygen content of 20% was introduced. The pressure was controlled at 500 Pa and the temperature was kept at this temperature for 40 minutes to obtain Ti 3 C 2 Tx / TiO 2 Composite materials.
[0069] Ti 3 C 2 Tx / TiO 2 The composite material was mixed with alcohol, ground and deposited on an aluminum oxide substrate containing an electrode by screen printing, and dried at 80°C for 6 hours to obtain a sensor.
[0070] Comparative Example 2
[0071] The difference between this comparative example and Example 1 is that the gas introduced during the oxygen microwave plasma is 100% pure oxygen. The specific method is as follows:
[0072] The MAX precursor Ti 3 AlC 2 Add to 80mL of 3mol / L hydrochloric acid and 0.05mol / L LiF solution, stir evenly and transfer to a 100mL polytetrafluoroethylene-lined stainless steel reactor, hydrothermally react at 120℃ for 5 days, centrifuge, wash and dry after cooling to obtain Ti 3 C 2 T x Powder; the obtained Ti 3 C 2 T x The powder was placed in a microwave plasma device, 100% pure oxygen was introduced, the pressure was controlled at 500 Pa, the power was turned on and the power was controlled at 700 W, and the oxygen microwave plasma treatment was performed for 40 min to obtain Ti 3 C 2 Tx / TiO 2 Composite materials.
[0073] Ti 3 C 2 Tx / TiO 2The composite material was mixed with alcohol, ground and deposited on an aluminum oxide substrate containing an electrode by screen printing, and dried at 80°C for 6 hours to obtain a sensor.
[0074] Comparative Example 3
[0075] The difference between this comparative example and Example 1 is that when the oxygen microwave plasma is carried out, the microwave power is high power (2000W), and the specific method is as follows:
[0076] The MAX precursor Ti 3 AlC 2 Add to 80mL of 4mol / L hydrochloric acid and 1mol / L LiF mixed solution, stir evenly and transfer to a 100mL polytetrafluoroethylene-lined stainless steel reactor, hydrothermally react at 120℃ for 5 days, centrifuge, wash and dry after cooling to obtain Ti 3 C 2 Tx (x = -F, -OH, -O) powder; the obtained Ti 3 C 2 The Tx powder was placed in a microwave plasma device, and an oxygen-argon mixed gas with an oxygen content of 20% (i.e., the volume fraction of oxygen in the oxygen-argon mixed gas was 20%) was introduced. The pressure was controlled at 500 Pa, and the power was turned on to control the power to 2000 W. After oxygen plasma treatment for 40 minutes, the powder was taken out to obtain Ti 3 C 2 Tx-TiO 2 Heterogeneous interface materials;
[0077] Ti 3 C 2 Tx-TiO 2 The heterogeneous interface material was mixed with alcohol, ground and deposited on an aluminum oxide substrate containing an electrode by screen printing, and dried at 80°C for 6 h to obtain a Ti 3 C 2 Tx-TiO 2 Hydrogen sensor with heterogeneous interface material as sensitive material.
[0078] 1. SEM morphology analysis
[0079] Figure 1 The Ti prepared by the hydrothermal method in Example 1 3 C 2 The morphology of Tx shows that Ti prepared by hydrothermal method 3 C 2 Tx has a two-dimensional accordion-like structure.
[0080] Figure 2 The oxygen microwave plasma treatment of Ti in Example 1 3 C 2Ti prepared after Tx 3 C 2 Tx-TiO 2 The morphology of the heterogeneous interface material shows that Ti 3 C 2 T x During the oxygen plasma treatment, the oxygen in the plasma will react with Ti 3 C 2 T x The -F functional groups on the surface compete with each other and gradually replace them. The detached F atoms are adsorbed on the anatase TiO2 that is initially oxidized. 2 Particle surface, inhibiting TiO 2 Along the (001) direction of crystal growth, many two-dimensional TiO sheets are formed on the surface. 2 , tightly wrapped in Ti 3 C 2 Tx surface. The two-dimensional sheet structure has a higher specific surface area due to its thin planar structure, which is beneficial to the adsorption of gas molecules and provides more active sites for surface reactions, thereby improving the gas sensing performance.
[0081] Figure 3 Ti in Comparative Example 1 3 C 2 Tx / TiO 2 The morphology of the heterogeneous interface material shows that under conventional heating methods, Ti 3 C 2 Tx only generates part of TiO on the surface 2 Particles have a low specific surface area, which is not conducive to the adsorption of gas molecules and cannot provide more active sites for surface reactions, resulting in a decrease in gas sensing performance.
[0082] Figure 4 Ti in Comparative Example 2 3 C 2 Tx / TiO 2 The morphology of heterogeneous interface materials. When the oxygen ratio is too large, Ti 3 C 2 Tx will be over-oxidized and have a low specific surface area, which is not conducive to the adsorption of gas molecules and cannot provide more active sites for surface reactions, resulting in a decrease in gas sensing performance.
[0083] Figure 5 Ti in Comparative Example 3 3 C 2 Tx / TiO 2 Morphology of heterogeneous interface materials. When the microwave power is too large, Ti 3 C 2Tx will be over-oxidized and have a low specific surface area, which is not conducive to the adsorption of gas molecules and cannot provide more active sites for surface reactions, resulting in a decrease in gas sensing performance.
[0084] 2. Gas Sensing Performance Test
[0085] The performance test of the hydrogen sensor prepared by the present invention is carried out according to the method disclosed in the art, and the test is carried out in a gas-sensitive test device (KLUM-QM-104). The specific steps are: (1) Connect the sensor to the gas-sensitive test device, let air flow into the device to achieve stability, and record the resistance value R of the device in the air. a ; (2) Introduce H into the device 2 Until the resistance value reaches stability again, record the device at H 2 The resistance value R g ; (3) Re-introduce air into the device until the resistance reaches a stable state and the device completes a response recovery process. The response value (Response) is defined as: Response = R a / R g . Different H 2 The concentration is obtained by gas dilution method, and the test concentration is 0-10000ppm.
[0086] Figure 6 is Ti in Example 1 3 C 2 T x / TiO 2 The response recovery curve of the sensor prepared by heterogeneous interface material to 1000ppm hydrogen shows that the Ti 3 C 2 T x -TiO 2 The heterogeneous interface material has a higher response value and a faster response recovery time to hydrogen.
[0087] Table 1 shows the performance of the sensors prepared in Examples 1 to 5 and Comparative Examples 1 to 3 to 1000 ppm of H 2 response value and response recovery time.
[0088] Table 1
[0089] Response value (Ra / Rg) Response / Recovery Time(s) Example 1 22.5 10 / 45 Example 2 20.3 15 / 58 Example 3 21.2 12 / 49 Example 4 19.9 19 / 62 Example 5 20.8 18 / 60 Comparative Example 1 8.4 49 / 75 Comparative Example 2 12.4 35 / 66 Comparative Example 3 9.1 46 / 83
[0090] Note: In Table 1, R a is the resistance value of the gas sensor in the air (ohm: Ω), R g For gas sensors in H 2 The resistance value in ohms: Ω.
[0091] It can be seen from Table 1 that after oxygen plasma treatment, Ti 3 C 2 T x , TiO obtained by partial oxidation 2 The morphology is two-dimensional nanosheets and is tightly wrapped in Ti 3 C 2 T x When the surface is 2 The gas-sensitive response of the TiO2 was improved the most. 2 It is not a two-dimensional nanosheet and does not have a higher specific surface area, which is not conducive to the adsorption of gas molecules and cannot provide more active sites for surface reactions, resulting in a decrease in gas sensing performance.
[0092] Figure 7 is Ti in Example 1 3 C 2 T x -TiO 2 The sensor prepared by heterogeneous interface material is sensitive to 1000ppm H 2 , 1000ppm C 2 H 6 O, 1000ppm SO 2 、1000ppm CH 4 , 1000ppm CO, 1000ppm CO 2 The response value of Ti obtained after oxygen microwave plasma treatment 3 C 2 T x / TiO 2 The heterogeneous interface material has a high selectivity for hydrogen.
[0093] The above are only preferred specific embodiments of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A method for in-situ growth of Ti3C2Tx-titanium dioxide heterogeneous interface material, characterized in that: The Ti3C2Tx material is prepared by hydrothermal etching of Ti3AlC2 using a hydrochloric acid solution containing a fluorine compound as an etching solvent, wherein x = -F, -OH and -O; The Ti3C2Tx material is subjected to oxygen microwave plasma treatment to obtain the Ti3C2Tx-titanium dioxide heterogeneous interface material; When oxygen microwave plasma treatment is performed, the microwave power is 500-800W; The oxygen microwave plasma treatment is carried out in an atmosphere of oxygen-argon mixed gas, wherein the volume fraction of oxygen in the oxygen-argon mixed gas is 10-30%.
2. The method for in-situ growth of Ti3C2Tx-titanium dioxide heterogeneous interface material according to claim 1, characterized in that: When the oxygen microwave plasma treatment is performed, the microwave power is 500-700W.
3. The method for in-situ growth of Ti3C2Tx-titanium dioxide heterogeneous interface material according to claim 1, characterized in that: The concentration of hydrochloric acid in the hydrochloric acid solution of the fluorine-containing compound is 4-12 mol / L, and the concentration of the fluorine-containing compound is 1-2 mol / L.
4. The method for in-situ growth of Ti3C2Tx-titanium dioxide heterogeneous interface material according to claim 1, characterized in that: The fluorine-containing compound is one of LiF, NH4F and NaF.
5. The method for in-situ growth of Ti3C2Tx-titanium dioxide heterogeneous interface material according to claim 1, characterized in that: The temperature of the hydrothermal method is 120-180° C. and the time is 1-5 days.
6. The method for in-situ growth of Ti3C2Tx-titanium dioxide heterogeneous interface material according to claim 1, characterized in that: The oxygen microwave plasma treatment time is 10-60 minutes.
7. A Ti3C2Tx-titanium dioxide heterogeneous interface material, characterized in that: Prepared according to the method according to any one of claims 1 to 6.
8. The use of the Ti3C2Tx-titanium dioxide heterogeneous interface material according to claim 7 in the preparation of a gas sensor, characterized in that: The gas sensor is a hydrogen sensor.
9. A method for preparing a hydrogen sensor, characterized in that: The Ti3C2Tx-titanium dioxide heterogeneous interface material described in claim 7 is mixed with alcohol, ground and deposited on a substrate containing an electrode, and dried to obtain the hydrogen sensor.
10. The method for preparing a hydrogen sensor according to claim 9, characterized in that: The substrate includes one of aluminum oxide, zirconium oxide, polyimide and polyethylene terephthalate.
Citation Information
Patent Citations
Method of treatment with a microwave plasma
CA2366175A1
Treatment method of two-dimensional MXene material, product and gas sensitive sensor
CN111521649A
Exposed (001) crystal face titanium dioxide / titanium carbide nanosheet as well as preparation method and application thereof
CN113578355A
Gas sensor and preparation method thereof
CN117147636A
Cited By
TiCxO1-x powder capable of being absorbed by total solar spectrum light and preparation method of TiCxO1-x powder
CN121377024A